Development of a Genetic System for Marinobacter atlanticus CP1 (sp. nov.), a Wax Ester Producing Strain Isolated From an Autotrophic Biocathode - Bird, Lina J.; Wang, Zheng; Malanoski, Anthony P.; Onderko, Elizabeth L.; Johnson, Brandy J.; Moore, Martin H.; Phillips, Daniel A.; Chu, Brandon J.; Doyle, J. Fitzpatrick; Eddie, Brian J.; Glaven, Sarah M. (Frontiers in Microbiology, 2018)
Here we report on the development of a genetic system for Marinobacter sp. strain CP1, previously isolated from the Biocathode MCL community and shown to oxidize iron and grow as a cathodic biofilm. Sequence analysis of the small and large subunits of the 16S rRNA gene of CP1, as well as comparison of select conserved proteins, indicate that it is most closely related to Marinobacter adhaerens HP15 and Marinobacter sp. ES.042. In silico DNA-DNA hybridization using the Genome-to-Genome Distance Calculator predicts CP1 to be a new species of Marinobacter described here as M. atlanticus. CP1 is competent for transformation with plasmid DNA using conjugation with Escherichia coli donor strain WM3064 and constitutive expression of green fluorescent protein (GFP) is stable in the absence of antibiotic selection. Targeted double deletion mutagenesis of homologs for the M. aquaeoli fatty acyl-CoA reductase (acrB) and fatty aldehyde reductase (farA) genes resulted in a loss of production of wax esters, however, single deletion mutants for either gene resulted in an increase in total wax esters recovered. Genetic tools presented here for CP1 will enable further exploration of wax ester synthesis for biotechnological applications, as well as furthering our efforts to understand the role of CP1 within the Biocathode MCL community.